Intradural Extramedullary Spinal Metastasis of a Kidney Cancer: Case Report - Sarmento, Marina Piquet; Haas, Leandro José; Tutida, Letícia Saori; Marques, Natália Tozzi; Scramocin, Thaize Regina; Omar, Omar Ahmad; Giustina, Evelyn Della; Sartori, Felipe Trevisan; Camilo, Liz Caroline; Borille, Thaís Moura; Bernardes, Celso Itiberê; Boer, Vitor Hugo; Lara, Danielle; Cabral, Filipe Laurindo; Mello, Luís Renato (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2019)
Objective To report a case of intradural extramedullary metastasis originated from a kidney neoplasm. Metastases in this topography occur in a low frequency, especially considering that the primary tumor was located along the urinary system.Case Report A male adult begins to present with pain in the lower limbs and develops flaccid paraparesis of the pelvic limbs, also attacking the control of the sphincter. The patient had a previous history of right nephrectomy due to a kidney neoplasm. After investigation with imaging exams, a metastatic lesion was found to be the source of the symptoms. The patient was surgically treated by the neurosurgery team of the hospital.Conclusion Cases like this are not common, and considering the low incidence of these cases and the nonspecific symptoms, such as pain, we do not always come up with the hypothesis of a metastasis in this topography. The surgical treatment, although it is a palliative feature, has an important part in maintaining the performance and the quality of life of the patient.
Keywords: neoplasm metastasis; kidney neoplasms; intradural metastasis